2010
DOI: 10.1007/s10661-010-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

Water quantity and quality optimization modeling of dams operation based on SWAT in Wenyu River Catchment, China

Abstract: Water quantity and quality joint operation is a new mode in the present dams' operation research. It has become a hot topic in governmental efforts toward integrated basin improvement. This paper coupled a water quantity and quality joint operation model (QCmode) and genetic algorithm with Soil and Water Assessment Tool (SWAT). Together, these tools were used to explore a reasonable operation of dams and floodgates at the basin scale. Wenyu River Catchment, a key area in Beijing, was selected as the case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…The effect of dam discharge on water quality can be demonstrated through a time-series model. Zhang et al [55] showed that water resources increased by 134%, and the equivalent standard pollution index decreased by 38% at a downstream site of the Sha River Reservoir, and by 4% upstream of the Lutong floodgate. Increasing water discharge from dams before periods of flooding enhances river flow and is useful for preventing the accumulation of pollutants, which decrease the water quality.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of dam discharge on water quality can be demonstrated through a time-series model. Zhang et al [55] showed that water resources increased by 134%, and the equivalent standard pollution index decreased by 38% at a downstream site of the Sha River Reservoir, and by 4% upstream of the Lutong floodgate. Increasing water discharge from dams before periods of flooding enhances river flow and is useful for preventing the accumulation of pollutants, which decrease the water quality.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been used successfully for the Wenyu River catchment in China [10] and the Han River basin in Korea [37]. By using the inlet flow of a dam as its outlet flow for simulation, it can be considered as the natural flow without the presence of the dam.…”
Section: Swat Model Simulationsmentioning
confidence: 99%
“…(1) Analysis of aquatic organisms, water quality, water quantity, ecology, and other aspects of the water environment is conducted through field surveys (Muñoz et al 2005;Mallik and Richardson 2009;Zhao et al 2010); (2) exploration of the impacts of sluices and dams on river discharge, water quality, ecology, river structure, and other aspects of the water environment has been conducted through examination of historical data (Brandt 2000;Petts and Gurnell 2005;Gülbahar and Elhatip 2005;Kurunc et al 2006;William 2006;Braatne et al 2008); and (3) numerical simulation models, including mature hydrological models (such as the Solid and Water Assessment Tool (SWAT)) coupled with water quality models, mature water quality simulation models (such as the water quality analysis simulation program (WASP)), and other numerical simulation analyses have been used (Campbell et al 2001;Newham et al 2002;Chung et al 2008;Marcé et al 2010). Specifically, mature hydrological models, coupled with water quality models, have been used to analyze the impacts of discharged sewage on downstream water quality (Hayes et al 1998;Li and Zuo 2012;Zheng et al 2012;Zhang et al 2010Zhang et al , 2011Zhang et al , 2013; mature water quality simulation models have been used to calculate and analyze water quality and other aspects of the water environment (Di Toro et al 1983;Stow et al 2003;Jae 2010;Zheng et al 2010;Lai et al 2013); and (4) mechanism experiments have been carried out. Some researchers have carried out model experiments to analyze the impacts of sluice regulation on flow regimes, migration, and pollutant transformation (Zhang et al 2012), while others have conducted field experiments to study the change laws of water and sediment contaminants under different regulation conditions Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%